When Learning Outpaces Structure: A Live-Project Learning Loop for Human Resource Development in Event Organizer Companies - Indra Kuswara; Yudan Hermawan (Al-Qalam Institute, 2026)
Event-organizing companies operate on short, high-pressure projects that leave little room for formal training. How their employees build capability under these conditions remains largely unexamined in workplace learning and human resource development research. This study examines workplace learning as a human resource development strategy within an event organizer company. It focuses on how experiential engagement with project work, autonomy within defined limits, and cross-divisional collaboration combine to build employee capability. Data were gathered through a qualitative case study design using in-depth interviews with five managerial and operational informants, direct observation of live event execution, and internal documentation. These sources were triangulated into four consistent findings. Results show that competence accumulates primarily through live project experience and bounded decision-making autonomy, which is reinforced by cross-divisional collaboration during execution. Efforts to convert this learning into structured organizational practice remain early and uneven. These findings are synthesized into an original model, the live-project learning loop, which traces how operational pressure generates individual and collective learning that often remains trapped at the tacit level. The study extends transformative learning theory to a non-formal, project-based creative industry setting that has rarely been examined before. It shows that disorienting operational pressure can itself trigger transformative learning and that such learning becomes organizationally transformative only once a deliberate mechanism exists to capture it.